Integral education - Dhal, Pravat Kumar (New Delhi : A.P.H Publishing, 2011)
It is being increasingly realized that the traditional system of education is not at all suited to the needs of the times. Too much importance given to material progress and technological implementation without a corresponding growth and inner development has produced the present cultural and psychological crisis. The complexities of our life are increasing with intensity. Deficiencies in intellectual alertness and in the character of students, the spread of dissatisfaction and indiscipline, defects of a method of selection alomost exclusively based on examinations, have become visible and imposed for a new system of education. Sri Aurobindo and The Mother have set out the ideas for the new system. This system is called Integral Education. This integral approach looks at the whole man and whole of life. The different dimensions of Integral Education are Physical Education, Vital Education, Psychic and Spiritual Education. This work deals with the Integral Education in Odisha. There is not sufficient research work in this field. So, the author has taken keen interest to find out its utility or usefulness to the society.
Includes bibliography.
Keywords: Education -- Philosophy. -- India; Education -- India .; Education